PENGARUH LITERASI DIGITAL GURU DAN MANAJEMEN PEMBELAJARAN TERHADAP MINAT BELAJAR SISWA SMA SLUA SARASWATI 1 DENPASAR - Ni Luh Putu Cahayani; Putu Diah Asrida; Muhammad Rahmattullah (LP3M Universitas PGRI Mahadewa Indonesia, 2022)
This study aims to 1) analyze the effect of teacher digital literacy on student interest in learning at SMA SLUA Saraswati 1 Denpasar; 2) Analyzing the influence of learning management on students' interest in learning at SMA SLUA Saraswati 1 Denpasar; 3) Analyzing teachers' digital literacy skills and learning management on students' interest in learning at SMA SLUA Saraswati 1 Denpasar. The sampling technique used saturated sampling, namely all teachers at SMA SLUA Saraswati 1 Denpasar. The research model consists of digital literacy (X1), learning management (X2) as the independent variable, and students' learning interest (Y) as the dependent variable. Data collection techniques were carried out using questionnaires that were distributed directly. The method used in analyzing the data is correlation analysis and multiple regression with the help of the SPSS application. The results show (1) Teacher's Digital Literacy variable (X1) has an effect on Student Learning Interest (Y) this is based on the t-count value of 4.979 > 1.985. With a significant value of 0.000, the value is smaller than the specified significant level, namely (α = 0.05). (2) Learning Management variable (X2) has an effect on Students' Interest in Learning (Y) this is based on the t-count value of 5.129 > 1.985. With a significant value of 0.000, the value is smaller than the specified significant level, namely (α = 0.05). (3) Student Learning Interest (Y) variable F-count is 22.890 > F-table 3.09. With a significant value of 0.000, the value is smaller than the specified significant level, namely (α = 0.05). (4) the results of the determination test show that the amount of Adjusted R Square is 24.9%, the variation of Student Learning Interest (Y) is influenced by Teacher Digital Literacy (X1) and Learning Management (X2) while the remaining 75.1% is influenced by other factors. which were not included in this study.